2002
DOI: 10.1038/sj.eye.6700011
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation and sensorineural hearing loss

Abstract: Aims There is increasing evidence that pseudoexfoliation (PXF) not only affects ocular anterior segment structures, but may also be a systemic disease. This study was undertaken to assess the relationship between PXF and sensorineural hearing loss. Methods Patients with PXF were identified from hospital records and underwent complete ocular examination. The sum of pure-tone hearing thresholds measured at 1, 2 and 3 kHz (HTL 1,2,3 ) in each ear was compared with the ISO 7029 standard sexmatched, median age-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 19 publications
(25 reference statements)
5
69
0
5
Order By: Relevance
“…An overexpression of the basic fibroblast growth factor (bFGF), a disbalance of matrix metalloproteinases (MMPs)/tissue inhibitor of MMPs (TIMPs), and increased cellular and oxidative stress, describe a part of the pathological process that is characterized by an elastic microfibrillopathy. [5][6][7][8][9] Although there is no clear-cut evidence that the deposits would cause degeneration of the extraocular tissues, they have been associated with transient ischaemic attacks, 10 Alzheimer's disease, 11 asymptomatic myocardial dysfunction, 12 sensorineural hearing loss, 13 stroke, myocardial infarction, systemic hypertension, 14 and aneurysm of the abdominal aorta. 15 The purpose of this study was to investigate the prevalence of PEX syndrome in a Greek cataract population and its relation to glaucoma and coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…An overexpression of the basic fibroblast growth factor (bFGF), a disbalance of matrix metalloproteinases (MMPs)/tissue inhibitor of MMPs (TIMPs), and increased cellular and oxidative stress, describe a part of the pathological process that is characterized by an elastic microfibrillopathy. [5][6][7][8][9] Although there is no clear-cut evidence that the deposits would cause degeneration of the extraocular tissues, they have been associated with transient ischaemic attacks, 10 Alzheimer's disease, 11 asymptomatic myocardial dysfunction, 12 sensorineural hearing loss, 13 stroke, myocardial infarction, systemic hypertension, 14 and aneurysm of the abdominal aorta. 15 The purpose of this study was to investigate the prevalence of PEX syndrome in a Greek cataract population and its relation to glaucoma and coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…The current study also included objective methods of audiological diagnostics to evaluate most of the auditory pathway. Studies by Yazdani et al, Cahill et al, Shaban and Asfour, and Turacli et al found an increased prevalence of sensorineural hearing loss in pure-tone audiometry at frequencies important for speech (1, 2, 3 kHz) in patients with PEX in comparison to patients without PEX in groups that were homologous in terms of age and sex [3,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…4 It is thought to have a role in many systemic vascular disorders such as systemic hypertension, angina pectoris, myocardial infarction, abdominal aorta aneurysm, transient ischemic attack and cerebrovascular events, peripheral vascular diseases, Alzheimer disease, and sensory-neural hearing loss. [4][5][6][7][8][9][10][11] In PEX, ocular complications are well documented but the clinical importance of systemic manifestations is unknown.…”
Section: Introductionmentioning
confidence: 99%